Laugh your way to grace : reclaiming the spiritual power of humor - Sparks, Susan, 1962- (SkyLight Paths Pub., 2010)
"Laughter is the GPS system for the soul," poses Susan Sparks as she diagnoses our current condition of "spiritual geliophobia" the fear of laughter in the presence of God. We have forgotten the playful, joyful aspect of the Holy One. "For those who think God doesn't laugh, think platypus and blowfish," is her reminder to all who live life just a bit too seriously. This is a substantive, yet personal and funny look at the power of humor. With compelling stories from her life and "laughter interludes" sprinkled throughout, Susan tracks the various ways humor has been revered in ancient cultures and world religious traditions, explores why humor is rarely included in our images of God, highlights the ways that humor allows us to transcend our isolation and our barriers, and reveals the ways in which humor can be the "ark" that carries us when tragedy hits. The result is a powerful, humorous case for laughter as a spiritual, healing path.